Endoscopic transnasal removal of an intraconal foreign body using an image-guided surgical system. Issue 1 (1st January 2016) - Teh, Daphne; Mohamad, Nor Fadhilah; Lim, Elizabeth; Zulkiflee, A. B.; Narayanan, Prepageran; Kamalden, Tengku Ain
ABSTRACT: Foreign bodies lodged in the intraconal space of the orbit pose a surgical challenge due to its deep location behind the globe. Image-guided endoscopic transnasal surgery facilitates the localization of the metallic foreign bodies and enables its safe removal with minimal surrounding tissue damage and optic nerve injury.